Dolzarb Issues Of Preschool And Primary Education: Problems, Solutions And Development Prospects. - Sherqo’ziyeva Zarnigor (Euro Asian Journal Publishing, 2024)
This article discusses issues of continuity between preschool and primary education. Based on the analysis of scientific literature, the authors highlighted the stages of development of the problem of continuity between preschool and primary education and the main approaches to solving it.
Keywords: continuity; preschool education; primary education; modern education